2010
DOI: 10.1111/j.1526-4610.2009.01514.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of MS Presenting With SUNCT Status

Abstract: Various primary headache syndromes are seen in a higher proportion of individuals with MS. 1 SUNCT (short-lasting unilateral neuralgiform headache with conjunctival injection and tearing) is a rare type of trigeminal autonomic cephalgia (TAC). It is characterized by brief (5-240 seconds), unilateral attacks of stabbing or lancinating pain centered around the eye or temple, that are associated with marked autonomic symptoms. While initially thought to be idiopathic, with the development of modern neuroimaging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Follow‐up MRI T2WI revealed hyperintensities at the left trigeminal tract topography. These neuroimages support previous explanations of SUNCT's pathophysiology …”
supporting
confidence: 87%
“…Follow‐up MRI T2WI revealed hyperintensities at the left trigeminal tract topography. These neuroimages support previous explanations of SUNCT's pathophysiology …”
supporting
confidence: 87%
“…This variation in frequency might be explained by differences in study design and patient inclusion criteria. Ophthalmoplegic migraine-like headache [10], complicated migraine [11], short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT) [12], and cluster tic syndrome [13] have also been reported in single MS cases. Fragoso and Brooks [14] described a single case and Yetimalar et al [15] reported the cases of two young women with migraine onset as the only symptom of the first episode of MS.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary SUNCT/SUNA in a stricter sense has been related to vascular and infectious disorders, neoplasms, and other disorders (Table ) . Most frequently, SUNCT seems to be associated with pituitary adenomas showing a prevalence of 7% (three of 43 patients) in the case series of Cohen et al and 100% (five of five patients) in a series reported by Chitsantikul and Becker .…”
Section: Sunct/sunamentioning
confidence: 99%